Association between uric acid and aortic aneurysms: A two-sample Mendelian randomization study - Tuo Xu; Yongkang Wu; Changwei Zheng; Weijie Chen; Zhi Zhang (Clinical and Experimental Hypertension)
Objective Based on Mendelian randomization (MR) methods, this study aims to explore causal associations of uric acid (UA) levels with aortic aneurysms (AAs).Methods In this MR study, data on UA levels and gout were extracted from genome-wide association study (GWAS) meta-analysis conducted by UK Biobank (UKB) for European population and the Biobank Japan Project (BBJ) for Asian population. Summary statistics of AAs were obtained from different databases. Inverse variance weighted (IVW), weighted-mode, weighted median, MR-Egger, and MR-PRESSO methods were used to examine the potential causal association of UA with AAs.Results The IVW estimates indicated that elevated UA level was associated with higher AAA risk among the European population (OR = 1.315, 95%CI: 1.024–1.689). In the Asian population, the UA level was positively linked to the odds of AA (OR = 1.393, 95%CI: 1.061–1.829). In addition, sensitivity analyses through MR leave-one-out and single SNP effect methods showed that these results were relatively robust.Conclusions UA may be a potential risk factor for AAs, indicating that clinicians should focus on serum UA levels among populations with high-risk of AAs. Studies to reveal the true relationship between them and clarify the underlying mechanism are still needed in the future.